Effect of Tannin-based Natural Corrosion Inhibitors from Biomass Wastes on Carbon Steel: A Review - Radityan, Fatwa Tresna; Feriyanto, Dafit (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Corrosion of carbon steel frames is a major concern in the automotive industry, especially for motorcycles that are often exposed to harsh environments. As an eco friendly alternative to synthetic chemical-based corrosion inhibitors, this study evaluates the effectiveness of corn husk extract as a natural, tannin-based inhibitor. Corn husks were selected due to their abundant availability as agricultural waste and their active compounds with potential anti-corrosion properties. The extract was obtained using maceration, reflux, and ultrasonic methods, and tested in corrosive solutions of NaCl, HCl, and H₂SO₄. The inhibitor’s effectiveness was assessed using weight loss measurements and surface morphology analysis. Results showed that corn husk extract reached up to 100% inhibition efficiency at a 600 ppm concentration, particularly in NaCl solution. The tannins and phenolic compounds in the extract played a crucial role in forming a protective layer on the carbon steel surface. These findings highlight the strong potential of corn husks as a green base material for corrosion inhibitors, while also promoting the use of biomass waste in developing sustainable corrosion protection technologies for the automotive industry.